Pipunculus Latreille, 1802 (Diptera: Pipunculidae) of Colombia, with description of three new species and an updated key to males of the Neotropical species - Ramos-Pastrana, Yardany; Marques, Dayse Willkenia A.; Rafael, José Albertino (Zootaxa, 2023)
Pipunculus Latreille, 1802 is a cosmopolitan genus of big-headed flies (Pipunculidae), with nine known species in the Neotropical region, but completely unknown in Colombia. Three new species of Pipunculus are described from Colombia, namely Pipunculus caeruleus sp. nov. (type-locality: Páramo de Santa Inés, Belmira), P. chiminiguagua sp. nov. (type-locality: Cabaña Chaina, Santuario de Fauna y Flora Iguaque) and P. planus sp. nov. (type-locality: Los Mudos, Santuario de Fauna y Flora Iguaque). Illustrations and a new dichotomic key to the Neotropical species are presented. This paper increases the number of Neotropical Pipunculus to 11, five in South America and three in Colombia, which is now the South American country with the highest diversity of this genus.